Developing a rapid diagnosis and treatment centre: estimating impact on hospital resources. Issue 2 (26th February 2004) - Hardern, R; Taylor, A; Shelton, R; Russell, A
Abstract : Objectives: To determine the possible impact on hospital bed occupancy if a "rapid diagnosis and treatment centre" (RDTC) were operational; to determine the number of patients that such a unit should be able to accommodate to avoid delays in transfer to this unit. Design: Retrospective review of accident and emergency (A&E) department notes from consecutive adults over a 16 day period. Setting: City centre teaching hospital with 1330 beds and 105 000 A&E new attendees per annum. Main outcome measures: Total number of bed days saved per annum (and daily average, assuming no variation by season or day of the week) and the expected occupancy of the RDTC according to the time of day. Results: The expected daily bed saving was estimated to be 16. Average occupancy was expected to be between six and eight (with little diurnal variation) and a unit with 10 beds would be sufficiently large to avoid delays for 85% of patients transferred there from A&E. Conclusions: On the basis of a "paper exercise" an RDTC would be expected to be beneficial in terms of bed utilisation; careful evaluation of the effects of such a unit in operation should be undertaken.